Application Of Problem-Based-Learning Learning Model To Improve Problem-Solving Skills Mathematics - Panjaitan, Hendrikson; Sihaloho, Binner (Yana Research, 2024)
This study uses the Problem Based-Learning learning methodology on Linear Program material in class XI SMA Parulian 1 Medan to assess students' mathematical problem-solving abilities. The study is a classroom action research. This study uses the Problem Based-Learning method to improve students' mathematical linear program problem-solving abilities. This study involved 43 students of class XI AK/AP SMA Parulian 1 Medan. Before the action was taken, students were tested to determine their abilities and levels of difficulty. The results of the first test showed that 40 students (93.02%) from class XI obtained a score of <65% and 3 students (6.98%) obtained a score of ≥65% (TKPM learning completion criteria), with an average score of 9.97. The learning outcomes of TKPM I class XI AK/AP with the Problem Based-Learning model showed that 27 students (62.80%) achieved the classical learning completion date (≥65%), while 16 students (37.20%) did not achieve the TKPM completion date with an average score of 20. After improvements were made from cycle I to cycle II in class XI AK/AP, 38 students (88.37%) achieved the classical learning completion date (≥65%), while 5 students (11.63%) did not achieve the TKPM completion date with an average class score of 25.51. In cycle II, there was an increase in the completion score of the conventional class XI TKPM I learning outcome exam. The results showed that the Problem Based-Learning learning approach of SMA Parulian 1 Medan improved the mathematical problem-solving abilities of Linear Program students.